TANGGUNG JAWAB AYAH KANDUNG TERHADAP NAFKAH ANAK SETELAH PERCERAIAN DALAM TINJAUAN UU NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Khairunnisa; Sanusi, Nur Taufik; Kiljamilawati (Universitas Islam Negeri Alauddin Makassar, 2026)
Abstract Abstract The main problem in this thesis is how is the responsibility of the biological father for child support after divorce in the Review of Law Number 23 of 2003 concerning Child Protection (Case Study of Jampu Village, Liliriaja District, Soppeng Regency). The sub-problems are 1) How is the legal protection of children's rights after divorce according to Law Number 23 of 2002 concerning Child Protection in Jampu Village, Liliriaja District, Soppeng Regency? 2) What are the impacts and legal consequences of the biological father's negligence in providing the right to child support after divorce according to Law Number 23 of 2002 concerning Child Protection in Jampu Village, Liliriaja District? This type of research is classified as qualitative with the research approaches used are: normative Syar'i, juridical, and sociological. The data sources for this research are primary data sources and secondary data sources. Furthermore, the data collection methods used are observation, interviews, and documentation. Then, data processing and analysis techniques are carried out through three stages, namely: data reduction, data presentation, and drawing conclusions. The results of this study indicate that legal protection of children's rights after divorce in Jampu Village, Liliriaja District, Soppeng Regency has not been implemented properly, this is due to the economy and lack of public awareness and understanding of children's rights after divorce through an execution application at the Religious Court. And the negligence of the father in fulfilling his obligations to child support after divorce has a significant impact on the child's life, both in terms of finance, psychology, health, social, and emotion. Some children even drop out of school due to the economic limitations experienced by their mothers. Legally, fathers who neglect to provide support to children can be subject to criminal sanctions based on Law Number 35 of 2014 concerning Child Protection, with a maximum prison sentence of 5 years and/or a maximum fine of 100,000,000.00 Keywords: Consists Child Support, Child Protection, Father's Responsibility